2022
DOI: 10.1186/s12967-022-03768-y
|View full text |Cite
|
Sign up to set email alerts
|

Biological role of matrix stiffness in tumor growth and treatment

Abstract: In recent years, the biological role of changes in physical factors in carcinogenesis and progression has attracted increasing attention. Matrix stiffness, also known as ECM stress, is a critical physical factor of tumor microenvironment and remains alternating during carcinogenesis as a result of ECM remodeling through activation of cancer-associated fibroblasts and extracellular collagen accumulation, crosslinking and fibrosis. Different content and density of extracellular collagen in ECM endows matrix with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 140 publications
(158 reference statements)
0
48
0
Order By: Relevance
“…Collagens are the most abundant structural proteins in ECM, which provide support, mediate drug resistance, promote tumor progression and aggressive cell transformation, and affect the mechanics of the tissue (Tamayo-Angorrilla et al, 2022) Therefore, different content and density of collagens have a significant impact on tissue stiffness and its variation (Deng et al, 2022), which will be sensed by cancer cells (Mierke, 2021) and, hence, influence cancer progression (Cavo et al, 2016) The morphology, proliferation capacity and invasive ability of cancer cells change as a result of the mechanotransduction process of the physical signals send by the ECM stiffness (Deng et al, 2022). Moreover, ECM stiffness also has an impact on the response to cancer treatments (Tamayo-Angorrilla et al, 2022), by controlling the sensitivity of the tumor cells (Deng et al, 2022). Acerbi et al (2015) observed the collagen accumulation in breast cancer as well as the linearization and thickening of the interstitial collagen.…”
Section: Extracellular Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagens are the most abundant structural proteins in ECM, which provide support, mediate drug resistance, promote tumor progression and aggressive cell transformation, and affect the mechanics of the tissue (Tamayo-Angorrilla et al, 2022) Therefore, different content and density of collagens have a significant impact on tissue stiffness and its variation (Deng et al, 2022), which will be sensed by cancer cells (Mierke, 2021) and, hence, influence cancer progression (Cavo et al, 2016) The morphology, proliferation capacity and invasive ability of cancer cells change as a result of the mechanotransduction process of the physical signals send by the ECM stiffness (Deng et al, 2022). Moreover, ECM stiffness also has an impact on the response to cancer treatments (Tamayo-Angorrilla et al, 2022), by controlling the sensitivity of the tumor cells (Deng et al, 2022). Acerbi et al (2015) observed the collagen accumulation in breast cancer as well as the linearization and thickening of the interstitial collagen.…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…During carcinogenesis, the stiffness of ECM is continuously changing due to ECM remodeling, which involves activation of cancer-associated fibroblasts and excessive extracellular collagen deposition, crosslink, and fibrosis ( Keller et al, 2021 ; Deng et al, 2022 ; Tamayo-Angorrilla et al, 2022 ). Collagens are the most abundant structural proteins in ECM, which provide support, mediate drug resistance, promote tumor progression and aggressive cell transformation, and affect the mechanics of the tissue ( Tamayo-Angorrilla et al, 2022 ) Therefore, different content and density of collagens have a significant impact on tissue stiffness and its variation ( Deng et al, 2022 ), which will be sensed by cancer cells ( Mierke, 2021 ) and, hence, influence cancer progression ( Cavo et al, 2016 ) The morphology, proliferation capacity and invasive ability of cancer cells change as a result of the mechanotransduction process of the physical signals send by the ECM stiffness ( Deng et al, 2022 ). Moreover, ECM stiffness also has an impact on the response to cancer treatments ( Tamayo-Angorrilla et al, 2022 ), by controlling the sensitivity of the tumor cells ( Deng et al, 2022 ).…”
Section: Breast Tissue: Basic Concepts and Mechanical Propertiesmentioning
confidence: 99%
“…6 Additionally, the increased deposition and crosslinking of ECM components lead to a stiffened matrix, which contributes to tumor development and progression. [7][8][9] Substantial evidences have shown that increased matrix stiffness promotes invasion and metastasis of tumor cells, enhances immune cell infiltration, gives an impetus to stem cell differentiation and so on. [10][11][12] Intriguingly, recent findings indicate that there exists a correlation between matrix stiffness and chemotherapy resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Cell softness is a kind of biomechanical property; tumor tissue is usually stiffer than normal tissue due to abnormal production and the crosslinking of extracellular matrix proteins, but individual tumor cells are usually softer than non-malignant cells. Current research has proved that the reduction in tumor cell stiffness is related to the transformation, malignancy, and metastasis of cancer cells [ 47 , 48 ]. Therefore, we established a method based on the biomechanical screening and three-dimensional soft fibrin gel culture of functional cancer stem cells (defined as “tumor-repopulating cells”, TRC) [ 49 ].…”
Section: Potential Of Mps In Delivering Of Chemotherapy Drugs and Oth...mentioning
confidence: 99%